A letter to my younger self: understanding talented athletes` experiences of and future recommendations for seeking help for mental health difficulties - McLoughlin, E.; Arnold, R. (Psychology of Sport and Exercise, 2026)
Researchers have suggested that athletes are at-risk for mental health difficulties partly due to the stressors they encounter. Despite this, athletes may not acknowledge nor seek support for their mental health problems. The aim of this study is to explore talented athletes' experiences of seeking help for mental help difficulties, and their perceptions of the psychological services offered. Utilizing letter to self-methodology, 16 talented athletes (11 female; Mage = 25.27, SD = 7.95) were asked to write a letter to their younger self outlining their experiences of seeking help for mental health difficulties. Data were analyzed using reflexive thematic analysis, and five themes were generated: (1) Athletes have a tendency to bottle up feelings as a way to protect themselves; (2) Unable to identify signs and symptoms of mental ill-health; (3) Availability of sport psychology support has improved, but it is still insufficient; (4) Athletes are individual and should be treated as so; and (5) The sporting environment should attempt to develop cultural competency. Following this, a composite version of the letter was developed and presented to a selection of the original sample (n = 9). Member reflection interviews were then completed (Mduration = 63.07 min; SD = 11.15) to explore their responses to the letter. This study provides insight into athletes` current and desired mental health support. From the findings, a set of recommendations are forwarded to strengthen the provision of mental health support and provide athletes with earlier and tailored support.